Takziyah Al-nafs dalam Lagu “Tombo Ati” Karya Opick - Fauzaan Taufiqurrahma; Rayza Aulya Nahari; Sheilita Saputri; Zahra Mawaddah; Dadan Firdaus (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The song Tombo Ati by Opick is a religious musical work that functions not only as entertainment but also as a medium for spiritual reflection. From a Sufi perspective, the song represents values of spiritual healing (tazkiyah), self-surrender (tawakkul), and purification of the heart from negative traits. This study aims to analyze how the lyrics of Tombo Ati reflect the core concepts of Sufi ethics, particularly in relation to inner healing and spiritual tranquility. The study applies the theory of Sufi ethics by Imam Al-Ghazali and the semiotic approach of Roland Barthes to examine both denotative and connotative meanings in the lyrics. The findings indicate that Tombo Ati conveys profound messages about repentance, self-awareness, and surrender to God as pathways to inner peace. Furthermore, semiotic analysis reveals that the lyrics operate not only at a literal level but also at a symbolic level, representing a spiritual journey. The song serves as a reflective medium that encourages listeners to internalize Sufi values in daily life.